1991
DOI: 10.1115/1.2906563
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of Compressor Station Operation Including Centrifugal Compressor and Gas Turbine

Abstract: Dynamic simulation of the operation of a compressor station requires mathematical modeling of the dynamic behavior of the compressor unit and various piping elements. Such models consist of large systems of nonlinear partial differential equations describing the pipe flow together with nonlinear algebraic equations describing the quasi-steady flow through various valves, constrictions, and compressors. In addition, the models also include mathematical descriptions of the control system, which consists of mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Different models [10,[39][40][41][42][43][44] have been presented in literature dealing with modeling compression systems and set up of surge avoidance strategies. In Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different models [10,[39][40][41][42][43][44] have been presented in literature dealing with modeling compression systems and set up of surge avoidance strategies. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [39], a model was developed and applied to three test cases: a compressor surge protection control, a compressor start-up for a single unit compressor station and a compressor station set point change for a compressor station composed of two compressors in series. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic behavior of the system is described by the gas properties values in the nodes connecting two modules. The mathematical model used in this paper was developed by researchers in Ref [12,13], where the continuity and momentum conservation equations were utilized in their investigation. A typical schematic of a real industrial compression system is shown in Fig.…”
Section: Model Developmentmentioning
confidence: 99%
“…(3) Equation (3) represents the spool dynamics, is the driver unit moment of inertia, is the supplied driver moment which is an input to the system, and is the torque on the shaft from the compressor. The final expression of governing equations for implementing in the FORTRAN code can be acquired by some assumption and simplification, as stated below [12]:…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation